A Visualization Towards Oral Histology and Pathology Practical Classes - Existing Scenario and Imminent Trends - Jain, Neetu; Keshwar, Shashi; Shrestha, Ashish; Agrawal, Navin (Birat Journal of Health Sciences, 2024)
Introduction: Detailed knowledge is necessary in order to use dental anatomy, histology, and pathology in academic and clinical settings. Despite a competent, uniform academic curriculum and a passable infrastructure, there is still a disconnect between student comprehension and teacher preparation. Objective: To evaluate the difficulties dental students have learning the subject. Methodology: A cross-sectional survey was conducted among Students at College of Dental Surgery, In B.P. Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal. A semi-structured questionnaire was used to collect the socio-demographic data and to understand students’ interest in oral histology and oral pathology, to understand the difficulties encountered in slide identification and operating the microscope. Results: Out of 178 students, 161 participated in the study giving a response rate of 90.44%. Overall result shows a maximum positive response suggesting most of the students regularly attend classes and finish their assigned tasks. Here data suggests a mixed response, with some students having difficulty in slide identification and remembering the features although the students are quite comfortable with the use of microscopes. Conclusion: Understanding the slide and using the microscope effectively are a few of the difficulties that students encounter in oral biology and oral pathology. To improve student comprehension and proficiency in these areas, targeted interventions are necessary, as this study highlights these challenges.